Armchair Economist Economics and Everyday Life - Steven E Landsburg; LANDSBURG (Steven E) (New York Free Press)
Landsburg aims to show how economic thinking illuminates the entire range of human behaviour. But instead of focusing on the workings of financial markets and international trade, he looks at the details of daily life to reveal what the laws of economics tell us about ourselves.
Keywords: Economics